Status Sosial Ekonomi dan Pekerjaan Ibu sebagai Faktor Kunci Obesitas Balita di Jawa Tengah: Wawasan untuk Intervensi Gizi: Socioeconomic Status and Maternal Employment as Key Factors of Toddler Obesity in Central Java: Insights for Nutritional Interventions - Naintina Lisnawati; Dion Zein Nuridzin; Siti Fatimah Pradigdo; Suyatno Suyatno (Amerta Nutrition, 2025)
Background: Obesity in children under five years of age is an emerging public health concern in Indonesia, where birth history and family characteristics may play a significant role. Objectives: This study aimed to analyze factors associated with obesity among toddlers in Central Java, Indonesia, using data from the 2022 Indonesian Nutritional Status Survey (SSGI). Methods: A cross-sectional study was conducted with a weighted sample of 21,987 toddlers (aged 0–59 months) from six cities and 29 districts in Central Java. Independent variables included toddler characteristics (sex, stunting at birth), family factors (area of residence, socioeconomic status), and maternal factors (marital status, education, employment, weight monitoring). Complex samples analysis was performed using chi-square tests for bivariate associations and multiple logistic regression for multivariate analysis, with a significance level of α=0.05. Results: Obesity prevalence was low at 1.4% (n=304). Bivariate analysis identified significant associations with stunting at birth (p-value=0.024), socioeconomic status (p-value<0.001), maternal education (p-value<0.001), and maternal employment (p-value<0.001). In the multivariate model, higher socioeconomic status (aOR=1.94, 95% CI=1.34–2.83, p-value<0.001) and maternal employment (aOR=1.42, 95% CI =1.03–1.96, p-value=0.032) were significant predictors of obesity. Stunting at birth approached significance (aOR=0.44, 95% CI=0.19–1.02, p-value=0.056). Sex, area of residence, marital status, maternal education, and weight monitoring were not significant predictors of childhood obesity. Conclusions: Higher socioeconomic status and maternal employment are key risk factors for toddler obesity in Central Java.